Identification of the antiepileptic racetam binding site in the synaptic vesicle protein 2A by molecular dynamics and docking simulations - Correa-Basurto, José; Cuevas-Hernández, Roberto I.; Phillips-Farfán, Bryan V.; Martínez-Archundia, Marlet; Romo-Mancillas, Antonio; Ramírez-Salinas, Gema L.; Pérez-González, Óscar A.; Trujillo-Ferrara, José; Mendoza-Torreblanca, Julieta G. (Frontiers in Cellular Neuroscience, 2015)
Synaptic vesicle protein 2A (SV2A) is an integral membrane protein necessary for the proper function of the central nervous system (CNS) and is associated to the physiopathology of epilepsy. SV2A is the molecular target of the anti-epileptic drug levetiracetam (LEV) and its racetam analogues. The racetam binding site in SV2A and the non-covalent interactions between racetams and SV2A are currently unknown; therefore, an in silico study was performed to explore these issues. Since SV2A has not been structurally characterized with X-ray crystallography or nuclear magnetic resonance, a three-dimensional (3D) model was built. The model was refined by performing a molecular dynamics simulation (MDS) and the interactions of SV2A with the racetams were determined by docking studies. A reliable 3D model of SV2A was obtained; it reached structural equilibrium during the last 15 ns of the MDS (50 ns) with remaining structural motions in the N-terminus and long cytoplasmic loop. The docking studies revealed that hydrophobic interactions and hydrogen bonds participate importantly in ligand recognition within the binding site. Residues T456, S665, W666, D670 and L689 were important for racetam binding within the trans-membrane hydrophilic core of SV2A. Identifying the racetam binding site within SV2A should facilitate the synthesis of suitable radio-ligands to study treatment response and possibly epilepsy progression.